Graphene Magnetite Polymeric Nanocomposites (GMPN)-Array Sensor for Human Brain Tumour Detection Using Specific Absorption Rate (SAR) Technique - Jamlos, M.A.; Jamlos, M.F. (International Journal of Integrated Engineering, 2019)
Graphene Magnetic Polymeric Nanocomposites-Array sensor is successfully detecting human brain tumour based on Specific Absorption Rate technique. The technique associated with low cost, non-invasive and accurate in detecting tumour. The sensor consists of graphene as the radiating element and Polydimethylsiloxane Ferrite as the substrate in order to realize ultra-wide band radiation (2.5 GHz-12.2 GHz) with high energy (2.5dB-6.7dB) in microwave frequency ranges. Amount of energy absorbed by the human brain indicated the present of tumour. Human brain with tumour absorbed more energy and recorded higher SAR value (2.56 W/kg) compared with human brain without tumour (1.07 W/kg).